Urgensi Pengesahan RUU Energi Baru dan Terbarukan dalam Upaya Pengembangan Energi Yang Berkelanjutan - Wahyudi, Ikhsan; Farhan; Risnain, Muh.; Erwin, Yulias (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Energy consumption in Indonesia remains heavily reliant on fossil fuels, including oil, gas, and coal, while new and renewable energy sources are still considered alternatives. This dependence on fossil fuels presents at least three significant risks: 1) the exhaustion of current oil reserves, assuming no new discoveries are made; 2) price volatility and instability due to demand outstripping oil production; and 3) greenhouse gas (GHG) emissions from burning fossil fuels. Consequently, to support Indonesia’s commitment to sustainable energy development, the ratification of the Draft Law on New and Renewable Energy (RUU EBT) should be prioritized. This study aims to identify and analyze the urgency of ratifying RUU EBT in promoting sustainable energy development, as well as the regulatory framework within RUU EBT that emphasizes sustainability principles. The research employs a normative legal research methodology, incorporating statutory, conceptual, and case study approaches. The study’s findings reveal that the legal framework governing new and renewable energy (EBT) in Indonesia is currently fragmented across various laws and regulations. Moreover, the existing regulations issued by the Government related to EBT frequently undergo changes, which undermines their ability to provide a strong legal foundation and guarantee legal certainty. This is because they have not been comprehensively consolidated into a single law. Additionally, the implementation of EBT is guided by principles such as benefit, efficiency, justice, sustainability, resilience, sovereignty, independence, accessibility, participation, and integration.